Hands-on Azure cognitive services : applying AI and machine learning for richer applications - Price, Ed, 1978-; Masood, Adnan; Aroraa, Gaurav (Springer, 2021)
Use this hands-on guide book to learn and explore cognitive APIs developed by Microsoft and provided with the Azure platform. This book gets you started working with Azure Cognitive Services. You will not only become familiar with Cognitive Services APIs for applications, but you will also be exposed to methods to make your applications intelligent for deployment in businesses. The book starts with the basic concepts of Azure Cognitive Services and takes you through its features and capabilities. You then learn how to work inside the Azure Marketplace for Bot Services, Cognitive Services, and Machine Learning. You will be shown how to build an application to analyze images and videos, and you will gain insight on natural language processing (NLP). Speech Services and Decision Services are discussed along with a preview of Anomaly Detector. You will go through Bing Search APIs and learn how to deploy and host services by using containers. And you will learn how to use Azure Machine Learning and create bots for COVID-19 safety, using Azure Bot Service. After reading this book, you will be able to work with datasets that enable applications to process various data in the form of images, videos, and text. You will: Discover the options for training and operationalizing deep learning models on Azure Be familiar with advanced concepts in Azure ML and the Cortana Intelligence Suite architecture Understand software development kits (SKDs) Deploy an application to Azure Kubernetes Service.